Donepezil-induced QTc prolongation: A case report - Vogel, Samantha M. (Ment Health Clin, 2019)
BACKGROUND: Several psychoactive medications are known to cause QTc prolongation. Patient factors also increase the risk for QTc prolongation, including bradycardia, female sex, older age, metabolic abnormalities, and polypharmacy. Donepezil, a cholinesterase inhibitor, prolongs the QTc interval through a multimodal mechanism. PATIENT HISTORY: A 26-year-old African American female was admitted to the inpatient psychiatric hospital following a suicide attempt that was not an overdose. Past medical history was significant for major depression, traumatic brain injury, seizures, hemiplegia, gastroesophageal reflux disease, and tachycardia. Two baseline electrocardiograms (EKGs) were obtained showing normal QTc intervals. After several weeks, donepezil (5 mg by mouth once daily) was initiated for cognitive rehabilitation and titrated over 3 weeks to a dose of 20 mg. An EKG performed after the last dose change showed a prolonged QTc of 463 ms. Another follow-up EKG performed 9 days later showed further prolongation to 528 ms. Laboratory values were within normal limits during her hospital stay. Donepezil was discontinued completely, leading to normalization of the QTc interval. DISCUSSION: QTc prolongation and torsades de pointes have been identified in postmarketing case reports of donepezil. Instances of QTc prolongation have predominantly been documented in the geriatric population, primarily in those with additional risk factors. Additionally, current literature does not support the use of donepezil for neurocognitive rehabilitation in daily doses exceeding 10 mg. A temporal and causal relationship was observed between the initiation and titration of donepezil and development of QTc prolongation.